Rethinking Industry's Role in a National Emergency - Sodhi, ManMohan; Tang, Christopher (MIT Sloan Management Review, 2021)
The shortcomings of the U.S. Strategic National Stockpile were fully exposed during the COVID-19 pandemic, and they must be remedied before the next large-scale public health emergency. This will require government and industry to work together to build backup capacity and standby capability, not just more inventory.
Online resource; Title from title page (viewed May 27, 2021)